2012
DOI: 10.5047/eps.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Gravity changes associated with variations in local land-water distributions: Observations and hydrological modeling at Isawa Fan, northern Japan

Abstract: Gravity changes associated with variations in local land-water distributions have been observed at Isawa Fan in northern Japan, and modeled by hydrological equations. We solve the Richards equation numerically for the time variation in the vertical soil moisture distribution, which is then spatially integrated to estimate gravity changes due to the soil moisture distribution. In modeling Isawa Fan, we assume a simple hydrological model: a horizontally homogeneous soil in an infinite half-space. The estimated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
(76 reference statements)
1
14
0
Order By: Relevance
“…While the modeled gravity was qualitatively consistent with the observed steep gravity increase during rainfall and the subsequent gradual decrease after rainfall, the amplitude of the modeled gravity was only 75% (about 12 μGal) of the observed gravity, mainly because of the coarse three‐dimensional water distribution model for the undulating volcano [see Kazama and Okubo , , Figure 5]. On the other hand, Kazama et al [] applied the modeling procedures of Kazama and Okubo [] to Isawa Fan, one of flat regions in Japan, and succeeded in reproducing the time variation of soil moisture within its observation error, and the resultant gravity disturbance to within 1 μGal root‐mean‐square (RMS). These studies showed that the hydrological disturbances observed at Asama Volcano can be reproduced more accurately, as long as the three‐dimensional water distributions in the volcano are modeled realistically at a higher resolution.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…While the modeled gravity was qualitatively consistent with the observed steep gravity increase during rainfall and the subsequent gradual decrease after rainfall, the amplitude of the modeled gravity was only 75% (about 12 μGal) of the observed gravity, mainly because of the coarse three‐dimensional water distribution model for the undulating volcano [see Kazama and Okubo , , Figure 5]. On the other hand, Kazama et al [] applied the modeling procedures of Kazama and Okubo [] to Isawa Fan, one of flat regions in Japan, and succeeded in reproducing the time variation of soil moisture within its observation error, and the resultant gravity disturbance to within 1 μGal root‐mean‐square (RMS). These studies showed that the hydrological disturbances observed at Asama Volcano can be reproduced more accurately, as long as the three‐dimensional water distributions in the volcano are modeled realistically at a higher resolution.…”
Section: Introductionmentioning
confidence: 60%
“…The hydrological model addresses the spatiotemporal distributions of soil water and unconfined groundwater, which are the most dominant factors in the hydrological gravity disturbances observed on the ground [e.g., Creutzfeldt et al , ; Kazama et al , ]. Soil water, which lies between the ground surface and the water table of unconfined groundwater (i.e., in the unsaturated layer or the vadose zone; Figure ), is expected to infiltrate vertically according to the following diffusion equation (the so‐called Richard's Equation) [e.g., Jury and Horton , ]: ∂θ∂t=∂z[]Dv(θ)∂θ∂z+Kv(θ),where θ = θ ( x , y , z , t ) is the volumetric water content (m 3 /m 3 ) at position ( x , y , z ) and time t , varying between a minimum ( θ min ) and a maximum value ( θ max ).…”
Section: Hydrological Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The gravity changes attributable to perched water level changes are expressed as a linear function of the water level changes. In earlier studies, this simple approach was applied for data obtained using SGs . Although the groundwater level measured at a single location is not always representative at a field scale, the model simplicity produces some practical benefits.…”
Section: Resultsmentioning
confidence: 99%
“…For the gravity data obtained after the above corrections, we estimated a groundwater noise with the GWA-TER1D (Kazama et al 2012), incorporating the daily weather data of the AMeDAS during the 20-year observation period (Japan Meteorological Agency, http://www. data.jma.go.jp/obd/stats/etrn/index.php).…”
Section: Discussionmentioning
confidence: 99%